2019
DOI: 10.1007/s11325-019-01914-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of oral appliance therapy with moderate mandibular advancement on obstructive sleep apnea and upper airway volume

Abstract: Purpose To find out if a moderate protrusion with a mandibular advancement device (MAD) can significantly increase the upper airway volume and, further, what signs and symptoms of obstructive sleep apnea (OSA) can be improved by this maneuver. Methods There were 58 adults diagnosed with OSA who were referred for MAD therapy. The mean apnea-hypopnea index (AHI) was 19.2 (SD 8.6). Five indicators of signs and symptoms of OSA (AHI, oxygen saturation, snoring, daytime sleepiness, and health-related quality of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
6
9
0
3
Order By: Relevance
“…The soft tissue connections between the target organs within the palatoglossal and palatopharyngeal arches are tightened by the advanced projection of the mandible, resulting in an enlargement of this area, the oropharynx, justifying the major improvement of the oropharynx compared to the other regions, once the MAD is placed. Interestingly, the reduction of the AHI Pahkala et al 48 obtained in their sample was quite similar to the one of the present study, from 19.9 ± 8.7 to 6.4 ± 5.2. According to Shete et al, 49 the increased upper airway volume favours an increased airflow, which is responsible for the improved patient's symptoms and increased oxygen saturation level.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The soft tissue connections between the target organs within the palatoglossal and palatopharyngeal arches are tightened by the advanced projection of the mandible, resulting in an enlargement of this area, the oropharynx, justifying the major improvement of the oropharynx compared to the other regions, once the MAD is placed. Interestingly, the reduction of the AHI Pahkala et al 48 obtained in their sample was quite similar to the one of the present study, from 19.9 ± 8.7 to 6.4 ± 5.2. According to Shete et al, 49 the increased upper airway volume favours an increased airflow, which is responsible for the improved patient's symptoms and increased oxygen saturation level.…”
Section: Discussionsupporting
confidence: 91%
“…This augmentation was at the expense of mainly the oropharynx, which significantly augmented from 10.9 ± 4.8 to 12.7 ± 5.4 cm 3 . Several studies have observed similar results 48‐50 . Our results are parallel to the findings observed in Pahkala et al, 48 where with a similar design and under a CBCT diagnosis, they observed a significant increased oropharynx volume after the placement of the MAD, which significantly augmented the total volume of the upper airway.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, 44% of the patients completed treatment with less than five events/hour. Similar findings have been published by other authors [31,32].…”
Section: Discussionsupporting
confidence: 93%
“…The total increase of vertical interincisal dimension of the OAs ranged from 4 to 12 mm, with a mean of 5.6 mm. A recent study identified patients with larger overbite as significantly more likely to achieve complete response of OA treatment, hypothesising that increased vertical dimensions for these patients normalises the intermaxillary space for the tongue in the oral cavity 44 . However, a general conclusion should not be drawn that increased vertical dimension improves the effect of OA treatment.…”
Section: Discussionmentioning
confidence: 99%